STUDI PENINGKATAN PENJUALAN OMAH KOPI OMAJI KLEPU DENGAN PELAKSANAANTATA KELOLA KEUANGAN - Devense Daeli; Andhi Supriyadi (Media Bina Ilmiah, 2022)
Planning, organizing, directing, and supervising activities related to finance, such as procurement and use of business funds, are referred to as financial management. Businesses need good financial management to increase sales. This study analyzes qualitative descriptive data, Primary and secondary data sources obtained through documentation and interviews are utilized in this study. In order to obtain information, the business owner and employees of Omah Kopi Omaji Klepu were interviewed. The study's findings show that Omah Kopi Omaji Klepu has used financial management, but not fully, and needs to be improved because it implements very basic financial management. Financial management at Omah Kopi Omaji Klepu is budget planning and simple control because of the limited knowledge of the owner, so Omah Kopi Omaji Klepu does not implement reporting in its financial management. In addition, financial management to increase sales can be done by allocating funds intelligently for efficient marketing strategies, developing innovative products, and ensuring the availability of sufficient working capital to meet market demand properly.